2023
DOI: 10.1002/jobm.202200612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biosynthesized silver nanoparticles effects on expression levels of virulence and biofilm‐related genes of multidrug‐resistant Klebsiella pneumoniae isolates

Abstract: The emergence of multidrug‐resistant (MDR) strains of Klebsiella pneumoniae is associated with high morbidity and mortality due to limited treatment options. This study attempts to biologically synthesize silver nanoparticles (AgNPs) and investigate their effect on expression levels of virulence and biofilm‐related genes in clinically isolated K. pneumoniae. In this study, biofilm formation ability, antibiotic resistance pattern, extended‐spectrum β‐lactamases (ESBLs), and carbapenemases production were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The suppression of bio lm formation may be the result of SFELS-AgNPs penetrating the bacterial cell wall, suppressing the synthesis of exopolysaccharide layers, and interfering with cell adhesion and communication [49]. Mousavi et al, recently studied bio lm reduction in K. pneumonia strains using biologically synthesized silver nanoparticles their results are comparable with this study as they have obtained signi cant reduction at 128 µg/mL of nanoparticles [50]. Additionally, prior research indicated that these NPs might be effective antibacterial agents against a variety of bacterial infections, such as K. pneumoniae [51].…”
Section: Effect Of Sfels-agnps On K Pneumonia Bio Lm Formationsupporting
confidence: 71%
“…The suppression of bio lm formation may be the result of SFELS-AgNPs penetrating the bacterial cell wall, suppressing the synthesis of exopolysaccharide layers, and interfering with cell adhesion and communication [49]. Mousavi et al, recently studied bio lm reduction in K. pneumonia strains using biologically synthesized silver nanoparticles their results are comparable with this study as they have obtained signi cant reduction at 128 µg/mL of nanoparticles [50]. Additionally, prior research indicated that these NPs might be effective antibacterial agents against a variety of bacterial infections, such as K. pneumoniae [51].…”
Section: Effect Of Sfels-agnps On K Pneumonia Bio Lm Formationsupporting
confidence: 71%
“…One study found that in resistant Klebsiella pneumoniae strains, the expression of the efflux pump gene OxqAB was decreased by both commercial and biosynthesized Ag NPs (Dolatabadi et al, 2021). What is more, Ag NPs were potential NPs that showed excellent reduction of biofilm-related genes (fimH, rmpA, and mrkA) in K. pneumoniae (Mousavi et al, 2023). Wang et al, developed the Ag NP-functionalized titanium implant surface.…”
Section: Ag Npsmentioning
confidence: 99%
“…Other properties of nanoparticles identified as responsible for antibiofilm roles are given by shape, surface charge, and composition. The adherence of bacteria is inhibited by using surfaces with nano-roughness [28,29,59].…”
Section: Introductionmentioning
confidence: 99%